ANALISIS PERBANDINGAN ASAM URAT BERDASARKAN POLA MAKAN PADA VEGETARIAN DAN NON VEGETARIAN DI MINAHASA - Priscillia Saluy (Jurnal Skolastik Keperawatan, 2019)
Abstract The purpose of this study is to know the comparison value of uric acid level according the eat pattern between the vegetarian and non vegetarian in Minahasa. Research design using T-test independent and ANOVA. The total sample is 37 respondent who vegetarian and 37 responden who non-vegetarian. The result of this study is there is a significant relationship of uric acid level between vegetarian and non vegetarian with significant value 0,001<0,05 and according to the eat pattern there is no significant relationship of uric acid level with the significant value 0,856>0,05. Conclusion of this study only there is a significant relationship of uric acid level between vegetarian and non vegetarian whereas eat pattern there is no significant telationship. Key words: uric acid, eat pattern, vegetarian, non vegetarian.